African Journal of Environmental Economics and Management ISSN 2375-0707 Vol. 7 (1), pp. 001-010, January, 2019. © International Scholars Journals - Oladele A. Ogunseitan; Timothy R. Smith (African Journal of Environmental Economics and Management, 2019)
The pervasiveness of human health impacts and ecosystem effects of lead (Pb) is not controversial, but there are serious arguments about the pace at which Pb should be eliminated from consumer products. Presumably, these arguments can be resolved by converting costs and benefits of Pb use to similar units, a notorious methodological challenge for health impacts in developing countries. To estimate the costs of Pb poisoning attributable to petrochemicals in Nigeria, we conducted a meta-analysis of measured blood lead levels (BLL) and we used published Relative Risk values for disease categories to estimate the proportion of overall disease burden attributable to Pb. We modeled the health costs of Pb exposure and we compared this to the cost of banning Pb. We estimate that Pb exposure accounts for 7 25% of the disease burden among Nigerian children, costing the health and education sectors 0.38 – 1.15 billion year-1 for every 1 mg/dL increase in BLL. In comparison, we estimate that a Pb abatement program in Nigeria will cost 0.076 – 0.23 billion year-1. If a Pb phase-out program is instituted now to lower the national BLL to 1 mg/dL by 2020, a savings of 2.7-8.0 billion would be realized.